Pyrosequencing and phenotypic microarray to decipher bacterial community variation in Sorghum bicolor (L.) Moench rhizosphere - Kumar, Ashwani; Dubey, Anamika; Malla, Muneer Ahmad; Dames, Joanna (Current research in microbial sciences, 2021)
•Different cultivation practices and climatic conditions play an important role in governing and modulating soil microbial communities.•This work, investigated the changes in bacterial community composition at taxonomic and functional level in rhizosphere soil of sweet sorghum under extensive cultivation practices at three different field sites of South Africa.•16S rRNA amplicon sequencing data revealed that at the phylum level, the dominant group was Cyanobacteria with a relative abundance of 63.3%, 71.8% and 81.6% from ASHSOIL1, ASHSOIL2, and ASHSOIL3, respectively.•Community-level physiological profiling (CLPP) analysis revealed that the metabolic activity of the bacterial community in ASHSOIL3 was the highest, followed by ASHSOIL1 and ASHSOIL2.•Overall, this study showed that soil pH, nutrient availability and cultivation practices played significant roles in governing the bacterial community composition in sorghum rhizosphere. Different cultivation practices and climatic conditions play an important role in governing and modulating soil microbial communities as well as soil health. This study investigated, for the first time, keystone microbial taxa inhabiting the rhizosphere of sweet sorghum (Sorghum bicolor) under extensive cultivation practices at three different field sites of South Africa (North West-South (ASHSOIL1); Mpumalanga-West – (ASHSOIL2); and Free State-North West – (ASHSOIL3)). Soil analysis of these sites revealed differences in P, K, Mg, and pH. 16S rRNA amplicon sequencing data revealed that the rhizosphere bacterial microbiome differed significantly both in the structure and composition across the samples. The sequencing data revealed that at the phylum level, the dominant group was Cyanobacteria with a relative abundance of 63.3%, 71.8%, and 81.6% from ASHSOIL1, ASHSOIL2, and ASHSOIL3, respectively. Putative metabolic requirements analyzed by METAGENassist software revealed the ASHSOIL1 sample as the prominent ammonia degrader (21.1%), followed by ASHSOIL3 (17.3%) and ASHSOIL2 (11.1%). The majority of core-microbiome taxa were found to be from Cyanobacteria, Bacteroidetes, and Proteobacteria. Functionally, community-level physiological profiling (CLPP) analysis revealed that the metabolic activity of the bacterial community in ASHSOIL3 was the highest, followed by ASHSOIL1 and ASHSOIL2. This study showed that soil pH and nutrient availability and cultivation practices played significant roles in governing the bacterial community composition in the sorghum rhizosphere across the different sites.